Acidic Activated Charcoal Prevents Obesity and Insulin Resistance in High-Fat Diet-Fed Mice - Zhang, Xuguang; Diao, Pan; Yokoyama, Hiroaki; Inoue, Yoshiki; Tanabe, Kazuhiro; Wang, Xiaojing; Hayashi, Chihiro; Yokoyama, Tomoki; Zhang, Zhe; Hu, Xiao; Nakajima, Takero; Kimura, Takefumi; et al. (Frontiers in Nutrition, 2022)
Obesity is becoming a major public health problem worldwide. Making charcoal from wood (“Sumi-yaki”) has been a traditional activity in the southern part of Nagano Prefecture for centuries, with activated charcoal having reported detoxifying effects. However, it is unclear whether activated charcoal also possesses anti-obesity properties. Additionally, since activated charcoal is usually alkaline and might be affected by gastric juice, we evaluated the effect of acidic activated charcoal on high-fat diet (HFD)-induced obesity. This study demonstrated that co-treatment of acidic activated charcoal with a HFD significantly improved obesity and insulin resistance in mice in a dose-dependent manner. Metabolomic analysis of cecal contents revealed that neutral lipids, cholesterol, and bile acids were excreted at markedly higher levels in feces with charcoal treatment. Moreover, the hepatic expressions of genes encoding cholesterol 7 alpha-hydroxylase and hydroxymethylglutaryl-CoA reductase/synthase 1 were up-regulated by activated charcoal, likely reflecting the enhanced excretions from the intestine and the enterohepatic circulation of cholesterol and bile acids. No damage or abnormalities were detected in the gastrointestinal tract, liver, pancreas, and lung. In conclusion, acidic activated charcoal may be able to attenuate HFD-induced weight gain and insulin resistance without serious adverse effects. These findings indicate a novel function of charcoal to prevent obesity, metabolic syndrome, and related diseases.